Enhancement of CO2 hydrogenation to formate using formate dehydrogenase immobilized on UiO66 and its derivatives - Shadeera Rouf; Yaser E. Greish; Bart Van der Bruggen; Sulaiman Al-Zuhair (Green Synthesis and Catalysis, 2025)
In the present work, a highly stable zirconium-based metal-organic framework (MOF), UiO66, and its derivative, UiO66-NH2, were tested as support materials to immobilize Formate dehydrogenase (FDH) for use in CO2 hydrogenation. Both physical adsorption and cross-linking approaches were tested for immobilization. Cross-linking with glutaraldehyde has been suggested to enhance the stability of the enzyme and reduce leaching, which is prone to physical attachment. The adsorption isotherm and kinetics were best described by Sips and pseudo-second-order models, respectively. The influences of the secondary structure of the protein on catalytic performance and formate production were studied. Immobilization of FDH resulted in a change in the secondary structure, with the α-helical content increased from 29.4 ​% of the free enzyme to 43 ​% after immobilization on UiO66 and 100 ​% after immobilization on UiO66-NH2. This structural change significantly enhanced the enzyme activity. At optimum conditions of pH 5.5 and 30 ​mM NaHCO3, the activity of immobilized FDH was 19.6 times higher than that of free FDH. Formate production was also enhanced using immobilized FDH on UiO66-NH2, where production was 2.4 times higher than that achieved using free FDH. Better stability and reusability were achieved by cross-linking with glutaraldehyde. The results of this work provide a novel insight into the changes in the secondary structure of FDH after immobilization and its positive effect on catalytic efficiency. These findings are expected to pave the way for the commercial applications of FDH for CO2 utilization.